EFEKTIVITAS KOMUNIKASI VERBAL DAN NONVERBAL DALAM PEMBELAJARAN MUFRADAT BAHASA ARAB PADA PESERTA DIDIK MADRASAH TSANAWIYAH - Hamzah Fathurrohman; Ade Nandang (STKIP Subang, 2026)
This study aims to analyze the effectiveness of verbal and nonverbal communication in teaching Arabic vocabulary (mufradat) to students at the Islamic junior secondary school level. The research employed a qualitative approach using a descriptive method and was conducted at Madrasah Tsanawiyah Al-Ma’arif Purwakarta, with ninth-grade students as the research subjects. Data were collected through observation and interviews. The findings revealed that verbal communication was implemented through explaining vocabulary meanings, providing sentence examples, conducting question-and-answer sessions, pronunciation exercises, and giving instructions. Meanwhile, nonverbal communication was manifested through the use of hand gestures, facial expressions, eye contact, body language, and visual media. Both forms of communication played a significant role in helping students understand and retain Arabic vocabulary. Verbal communication provided conceptual understanding, whereas nonverbal communication reinforced meaning through visual representation. The study further found that the integrated use of verbal and nonverbal communication effectively enhanced students’ comprehension, participation, and mastery of Arabic vocabulary. Therefore, teachers should optimize both forms of communication to improve the effectiveness of Arabic language learning.